Associação entre características do temperamento com os níveis de percepção de competência e desempenho motor de crianças - Martins, Aline de Oliveira (2017)
The aim of this study was to verify if temperament characteristics are associated to the different levels of perception of competence and motor performance of children of six and seven years of age. Participated 182 children, belonging to the municipal schools of a municipality of the Central Region of the state of Rio Grande do Sul and their respective parents. The Children's Behavior Questionnaire (CBQ) verified the temperament characteristics, the Pictorial Scale of Perceived Competence and Social Acceptance, verified the child's perceptions of competence and the Test of Gross Motor Development - Second Edition (TGMD-2) assessed motor performance. Descriptive statistics were used for the presentation of variables and for associations with simple linear regression, with significance level of p ≤ 0.05. The results showed greater presence of extroversion characteristics, control with effort and less presence of negative affection for the temperament variable. Competence perception presented high scores in the cognitive (53.3%), social (52.2%), motor (53.3%) and maternal (52.7%) and unsatisfactory classifications (88.5%) For motor performance. Regarding the associations between the temperament characteristics and the perception of competence, it identified an association in the cognitive domain with the levels of perceptual sensitivity and lower levels of sadness and pleasure in performing low intensity activities. The social domain associated with the perceptual sensitivity and the motor domain with the characteristics of pleasure in the accomplishment of activities with low intensity and the lower levels of sadness and shyness. The domain of maternal acceptance cannot be explained by the temperament characteristics. The characteristic of pleasure temperament in performing low intensity activities was significant and important in the locomotion model. Approximation, activity level and low intensity pleasure were important in the object control skills model and the pleasure of high intensity, activity level and low intensity pleasure for the QMG model. The regression model between the domains of competence perception and motor performance verified that the locomotion skills are not explained by the domains of competence perception. However, object control and QMG were significant with the domains of cognitive and motor, however, with low level of importance in the model. It was concluded that the perceptions of competence were associated with the levels of motor performance and with the dimension of extroversion (high intensity pleasure), control with effort (perceptual sensitivity and low intensity pleasure) and the lower levels of some characteristics of Negative affect (sadness and shyness). On the other hand, the motor performance levels were only associated with some characteristics of the extroversion dimension. In this sense, understanding the dimensions of temperament and perception of competence can help in the identification of individuals with motor risk and propose motor interventions for the child according to their needs.